He stopped loving her today : George Jones, Billy Sherrill, and the pretty-much totally true story of the making of the greatest country record of all time - Isenhour, Jack (American made music series., 2011)
When George Jones recorded "He Stopped Loving Her Today" more than thirty years ago, he was a walking disaster. Twin addictions to drugs and alcohol had him drinking Jim Beam by the case and snorting cocaine as long as he was awake. Before it was over, Jones would be bankrupt, homeless, and an unwilling patient at an Alabama mental institution. In the midst of all this chaos, legendary producer Billy Sherrill-the man who discovered Tammy Wynette and cowrote "Stand by Your Man"--Would somehow coax the performance of a lifetime out of the mercurial Jones. The result was a coun